2008
DOI: 10.1021/ja805681w
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Circularly Polarized Luminescence Activity Exhibited by Cesium Tetrakis(3-heptafluoro-butylryl-(+)-camphorato) Eu(III) Complexes in EtOH and CHCl3 Solutions

Abstract: Circularly polarized luminescence (CPL) spectroscopy is the emission analogue to circular dichroism (CD) spectroscopy. 1 It is common to report the degree of CPL in terms of the luminescence dissymmetry factor, g lum (λ), which is defined as follows: g lum (λ) = 2ΔI/I = 2 (I L -I R )/(I L + I R ), where I L and I R refer respectively to the intensity of left and right circularly polarized emissions. A value of 0 for g lum corresponds to no circular polarization, while the absolute maximum value is 2. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
268
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 309 publications
(278 citation statements)
references
References 8 publications
9
268
0
1
Order By: Relevance
“…Circularly polarised luminescence studies will be carried out in future work to investigate the influence of the concentration and of chirality on the photophysical properties. [23] In summary, we have reported a rare enantiopure trinuclear europium complex obtained in a novel concentrationdependent self-assembly process promoted by a new (S)-Phbipox À ligand. We have shown that selective homochiral recognition occurs, probably as a result of sterical interaction, during the self-assembly of the bis-ligand monomeric complexes to yield the final trinuclear species.…”
Section: In the [(Ddd)-{eu((s)-phbipox) 2 } 3 ]mentioning
confidence: 88%
“…Circularly polarised luminescence studies will be carried out in future work to investigate the influence of the concentration and of chirality on the photophysical properties. [23] In summary, we have reported a rare enantiopure trinuclear europium complex obtained in a novel concentrationdependent self-assembly process promoted by a new (S)-Phbipox À ligand. We have shown that selective homochiral recognition occurs, probably as a result of sterical interaction, during the self-assembly of the bis-ligand monomeric complexes to yield the final trinuclear species.…”
Section: In the [(Ddd)-{eu((s)-phbipox) 2 } 3 ]mentioning
confidence: 88%
“…Up to now, the highest levels of CPL have been mainly achieved from chiral lanthanide complexes, 2d–e,8d–f which typically exhibit | g lum | values within the 0.05–0.5 range (an exceptional value of 1.38 has been reported for an europium(III) complex). 14 However, the emission efficiencies of these complexes are usually small, due to the nature of the involved metal-centered electronic transitions. This fact makes difficult their use in certain CPL applications ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…12 Among various chiral luminescent molecular systems investigated, Eu(III) complexes exhibit high g lum values, with ∼1.3 being the highest reported until date in cesium tetrakis(3-heptafluoro-butylryl-(+)-camphorato) Eu(III) complexes. 13 In contrast to inorganic complexes, the advantage with organic molecules is that their emission can be readily tuned by bringing about modulations in their excited state electronic levels. The modulations in the electronic states have been achieved by processes such as self-assembly, by chemical transformations of the substituents, and by changing the environment through external stimuli.…”
mentioning
confidence: 99%